Lithium battery diaphragm with functional coating on surface and preparation method of lithium battery diaphragm
By preparing functional coatings on the surface of the lithium battery separator and spraying two-dimensional nanomaterials using ultrasonic spraying technology, the cycle stability and safety issues of lithium metal secondary batteries are solved, and more uniform lithium ion deposition and longer cycle life are achieved.
Patent Information
- Application Number
- CN202411926015.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The cycle stability of lithium metal secondary batteries is insufficient, the cycle life is short, and the safety performance is poor, which is mainly caused by the uneven dissolution-deposition behavior of lithium ions.
Functional coatings are prepared on the surface of the lithium battery separator, and a two-dimensional nanospray material containing nitride or oxide is sprayed on the surface of the separator by ultrasonic spraying to form a uniform protective layer.
By regulating the deposition process of lithium ions, the cycle stability and safety of the battery can be improved and the cycle life will be extended.
Smart Images

Figure CN119764745A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium battery materials, and in particular relates to a lithium battery separator having a functional coating on its surface and a preparation method thereof. Background Art
[0002] The rapid development of human society has put forward higher demands on new energy storage systems, among which high energy density secondary batteries have become one of the most important energy storage technologies. In particular, secondary batteries using lithium metal with high theoretical specific capacity and low reduction potential as negative electrodes have great development potential. However, there is still a huge gap between the actual performance and theory of the current lithium metal secondary battery system, which is mainly manifested in insufficient cycle stability, short cycle life, poor safety performance and other problems. One of the main causes of these problems is the lithium metal electrode. Lithium metal itself has a high reactivity. During the battery's charge and discharge cycle reaction, the excessive reactivity of lithium metal will lead to differences in current density and liquid phase mass transfer rate in different areas of the electrode surface, which will cause uneven dissolution-deposition behavior of lithium ions. This will lead to a series of performance degradation and safety hazards, from reduced coulomb efficiency and shortened cycle life to the generation of dendrites, short circuit fire, etc., which greatly limits the efficient use of lithium metal electrodes. How to more effectively regulate the dissolution-deposition behavior of lithium ions is the core of the problem. The present invention proposes to prepare a functional coating on the surface of a battery separator, hoping to improve the safety and cycle stability of lithium batteries by improving the physical properties of the separator and regulating the electrode reaction process of lithium ions by the active coating material. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a lithium battery separator having a functional coating on its surface and a preparation method thereof.
[0004] The technical solution adopted by the present invention is: a method for preparing a lithium battery diaphragm with a functional coating on the surface, using an ultrasonic spraying method to spray a two-dimensional nano-spraying material containing nitride or oxide on the surface of the battery diaphragm to form a uniform protective layer.
[0005] Preferably, the spraying liquid includes a coating material, an adhesive and a dispersant; the coating material and the adhesive are mixed in a mass ratio of 8-10:1 and then added to the dispersant, and the mass fraction of the solid matter is 30-50 g / L.
[0006] Preferably, the coating material is at least one of molybdenum nitride, copper nitride, titanium nitride, nickel nitride, vanadium nitride, aluminum oxide, titanium oxide, silicon oxide and copper oxide.
[0007] Preferably, the coating material is in the shape of two-dimensional nanosheets, with a dimension in the thickness direction less than 10 nm and a dimension in the plane direction greater than 500 nm.
[0008] Preferably, the adhesive is at least one of polyurethane (TPU), polyacrylonitrile (PAN), polyethylene, polypropylene, poly(meth)acrylate, polymethyl (meth)acrylate, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroalkyl polymer (PFA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polysiloxane, polysilazane and polycarbosilane.
[0009] Preferably, the dispersant is at least one of ethylene glycol dimethyl ether (DME), N,N-dimethylformamide (DMF), dimethyl sulfone, diethyl sulfone, adiponitrile, tetrahydrofuran, N-methylpyrrolidone, acetonitrile, benzonitrile, 2-methyltetrahydrofuran, dioxolane, 4-methyldioxolane, N,N-dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, dichloroethane, chlorobenzene, ethanol, methanol and propanol.
[0010] Preferably, the diaphragm to be sprayed may be a base membrane without coating or a diaphragm with a ceramic coating already present.
[0011] Preferably, the ultrasonic spraying parameters are adjusted: the height of the nozzle from the diaphragm is 100-200mm; the nozzle moves at a speed of 50-100mm / s relative to the diaphragm, the spray liquid discharge speed is 0.5-2ml / min, and the ultrasonic power is 1-4W; after the parameters are set, start spraying; after starting spraying, the nozzle airflow needs to be kept stable at about 20L / min.
[0012] The invention discloses a method for preparing a lithium battery separator having a functional coating on its surface. The invention discloses a lithium battery separator having a functional coating on its surface.
[0013] A lithium battery comprises a lithium battery separator having a functional coating on its surface.
[0014] The advantages and positive effects of the present invention are: using an ultrasonic spraying method to spray two-dimensional nanomaterials on the surface of a battery diaphragm to form a uniform protective layer; the diaphragm coating prepared by this method has a unique nanostructure and material properties, and can regulate the lithium ion conduction and deposition process occurring between the diaphragm and the electrode interface, thereby improving the battery cycle stability and safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The SEM images of the diaphragm formed in Example 1 and Comparative Example 1 and the lithium metal negative electrode after cycling; wherein a is the SEM image of sample A; b is the SEM image of the negative electrode of the battery prepared using sample A after cycling; c is the SEM image of sample B; d is the SEM image of the negative electrode of the battery prepared using sample B after cycling;
[0016] Figure 2 This is a battery cycle performance diagram of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0017] The embodiments of the present invention are described below with reference to the accompanying drawings.
[0018] The present invention relates to a lithium battery diaphragm with a functional coating on the surface and a preparation method thereof. First, a spraying liquid containing a nitride or oxide spraying material, an adhesive and a dispersant is prepared, added to an ultrasonic spraying device, and sprayed on the surface of the diaphragm to form a functional coating. The ultrasonic spraying technology is used to construct a functional coating on the surface of the lithium battery diaphragm to improve the mechanical strength and thermal stability of the diaphragm. At the same time, the deposition process of lithium ions is regulated to form a uniform and dense deposition layer on the surface of the negative electrode, thereby improving the battery safety and cycle stability and extending the cycle life.
[0019] The specific preparation method is as follows:
[0020] Step 1: Preparation of spray liquid; weigh the coating material and the adhesive in a mass ratio of 8-10:1, mix them, and stir the mixture 1 evenly, wherein the mass ratio of the coating material and the adhesive is preferably 9:1; add the mixture 1 to the dispersant to form a suspension, wherein the mass fraction of the mixture 1 is 30-50g / L, preferably 40g / L, and form a spray liquid by sufficient stirring and ultrasonic dispersion;
[0021] Among them, the coating material is at least one of molybdenum nitride, copper nitride, titanium nitride, nickel nitride, vanadium nitride, aluminum oxide, titanium oxide, silicon oxide and copper oxide. Preferably, the coating material is a two-dimensional nanosheet morphology, with a thickness dimension less than 10nm and a plane dimension greater than 500nm. The two-dimensional nanosheet material will cover the diaphragm in the plane direction to form a coating. Only a thin coating material is needed to completely cover the surface of the diaphragm without leaving any gaps, thereby improving the puncture resistance of the diaphragm. The adhesive is polyurethane (TPU), polyacrylonitrile (PAN), polyethylene, polypropylene, poly(meth)acrylate, poly(methyl)acrylate, polytetrafluoroethylene (PTFE), At least one of polyvinylidene fluoride (PVDF), perfluoroalkyl polymer (PFA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polysiloxane, polysilazane and polycarbosilane; the dispersant is at least one of ethylene glycol dimethyl ether (DME), N,N-dimethylformamide (DMF), dimethyl sulfone, diethyl sulfone, adiponitrile, tetrahydrofuran, N-methylpyrrolidone, acetonitrile, benzonitrile, 2-methyltetrahydrofuran, dioxolane, 4-methyldioxolane, N,N-dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, dichloroethane, chlorobenzene, ethanol, methanol and propanol.
[0022] Step 2: Inject the prepared spray liquid into the ultrasonic spray equipment, lay the diaphragm to be sprayed on the work surface, the diaphragm to be sprayed can use an uncoated base membrane or a diaphragm with an existing ceramic coating; adjust the ultrasonic spray parameters: the height of the nozzle from the diaphragm is 100-200mm; the nozzle moves at a speed of 50-100mm / s relative to the diaphragm, the spray liquid discharge speed is 0.5-2ml / min, and the ultrasonic power is 1-4W; start spraying after the parameters are set; after starting spraying, it is necessary to keep the nozzle airflow stable, and the nozzle airflow can preferably be set to 20L / min; wait for 2-3min after spraying to allow the dispersant to volatilize, and finally form a functional coating on the surface of the diaphragm.
[0023] The two-dimensional nanomaterials are sprayed on the surface of the battery diaphragm by ultrasonic spraying to form a uniform protective layer. The diaphragm coating prepared by this method has a unique nanostructure and material properties. The two-dimensional nanosheet morphology material is used, so that the coating is in the form of two-dimensional nanosheets overlapping each other, which can regulate the lithium ion conduction and deposition process between the diaphragm and the electrode interface, and improve the battery cycle stability and safety.
[0024] First, it can improve the mechanical strength and thermal conductivity of the diaphragm; two-dimensional nanomaterials have high mechanical strength and thermal conductivity. After forming a coating on the surface of the diaphragm, it can improve the puncture resistance and thermal conductivity of the diaphragm, improve the resistance of the diaphragm to lithium dendrite puncture, reduce the local temperature rise of the battery, prevent lithium dendrites from piercing the diaphragm and the deformation of the diaphragm caused by heat aggregation, and improve battery safety. Secondly, the coating material is lithium-philic, and there is a strong interaction between the coating material and lithium ions, which can significantly reduce the nucleation overpotential of lithium ions. Coating it on the diaphragm can induce lithium ions to form a uniform deposition at the diaphragm-negative electrode interface. In addition, the coating material has high ionic conductivity. The coating material can undergo partial or complete redox reaction with lithium ions to generate corresponding metal elements and lithium compound phases with high ionic conductivity, which can even out the lithium ion flow and increase the lithium ion transmission rate, thereby improving the battery cycle stability.
[0025] Lithium battery separators with functional coatings on their surfaces can be used in lithium batteries. The functional coatings on the surface of the separators can regulate the lithium ion deposition process on the negative electrode surface. The coatings need to be placed on the interface between the separator and the negative electrode, and cannot be placed on the positive electrode side. Most high-energy lithium batteries use lithium metal as the negative electrode. Lithium metal has extremely high reactivity and reacts with water, oxygen and some chemical solvents in the air. Therefore, it is difficult to manufacture coatings on the surface of the negative electrode. The separators are stable in nature and suitable for adding functional coatings. The coating on the surface of the separator can be directly operated in an air atmosphere, and the process implementation is relatively easy, and it does not affect the role of the coating on the interface between the separator and the negative electrode after the battery is assembled. The prepared lithium battery separator with functional coatings on its surface can be assembled into a lithium battery. Under the action of the separator coating, the separator can show higher puncture resistance and lower thermal shrinkage. It can effectively stabilize the lithium metal electrode, inhibit the side reactions of lithium metal and electrolyte, reduce the formation of dendrites and dead lithium on the surface of the negative electrode, and enable the lithium battery to show a longer cycle life.
[0026] The scheme of the present invention is described below in conjunction with the accompanying drawings, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.
[0027] Example 1
[0028] 3.6g of molybdenum nitride nanosheets and 0.4g of polyvinylidene fluoride (PVDF) were mixed and stirred evenly, and then 100ml of N-methylpyrrolidone (NMP) was added thereto, and a spray liquid was formed by sufficient stirring and ultrasonic dispersion. The spray liquid was injected into the ultrasonic spray equipment, and the diaphragm to be sprayed was laid on the workbench. The diaphragm was selected to be a non-coated PE base film. The ultrasonic spray parameters were debugged: the height of the nozzle from the diaphragm was 150mm; the speed of the nozzle relative to the diaphragm was 80mm / s, the discharge speed of the spray liquid was 1.2ml / min, and the ultrasonic power was 1W. After the parameters were set, spraying began. After the spraying was completed, wait for 2 minutes for the dispersant to volatilize, and finally a functional coating was formed on the surface of the diaphragm, marked as sample A.
[0029] The above sample A was subjected to morphological analysis under a scanning electron microscope. Figure 1 a. Figure 1 b shows that a uniform coating of molybdenum nitride nanosheet material is formed on the surface of the sample A diaphragm, and a uniform and dense sediment layer is formed on the surface of the lithium metal negative electrode after cycling.
[0030] The above sample A was used to assemble a soft-package lithium metal battery, and the sample A separator was used with the NCM ternary positive electrode and the lithium metal negative electrode to manufacture a full battery. The prepared battery was subjected to a cycle performance test, and a cycle test was performed at 0.2C charging and 0.5C discharging under normal temperature and pressure. The test results are as follows Figure 2 As shown, the first discharge capacity is 3.50Ah, the 90th discharge capacity is 3.88Ah, and the capacity retention rate is 110.8%.
[0031] Comparative Example 1
[0032] The uncoated PE base film is marked as sample B. The morphology of sample B was analyzed under a scanning electron microscope; the results are shown in FIG. Figure 1 c. Figure 1 d shows that the surface of the sample B separator is a porous structure of a conventional base membrane, and a loose and porous sediment layer is formed on the surface of the lithium metal negative electrode after cycling.
[0033] The above sample B was used to assemble a soft-package lithium metal battery, and the sample B separator was used in combination with the NCM ternary positive electrode and the lithium metal negative electrode to manufacture a full battery. The prepared battery was subjected to a cycle performance test, and a cycle test was performed at 0.2C charging and 0.5C discharging under normal temperature and pressure. Figure 2 The test results showed that the first discharge capacity was 3.68Ah, the 80th discharge capacity was 3.32Ah, and the capacity retention rate was 90.2%.
[0034] Example 2
[0035] Mix 2.7g titanium nitride nanosheets and 0.3g polyvinylidene fluoride (PVDF) and stir evenly, then add 100ml N,N-dimethylformamide (DMF) to form a spray liquid through sufficient stirring and ultrasonic dispersion. Inject the spray liquid into the ultrasonic spray equipment and lay the diaphragm to be sprayed on the work surface (use uncoated PE base film). Debug the ultrasonic spray parameters: the height of the nozzle from the diaphragm is 130mm; the speed of the nozzle relative to the diaphragm is 60mm / s, the spray liquid discharge speed is 0.8ml / min, and the ultrasonic power is 1W. Start spraying after the parameters are set. After the spraying is completed, wait for 2 minutes for the dispersant to volatilize, and finally form a functional coating on the surface of the diaphragm.
[0036] Example 3
[0037] Mix 4.5g of alumina nanosheets and 0.5g of polymethyl methacrylate (PMMA) and stir evenly, then add 100ml of ethylene glycol dimethyl ether (DME) to form a spray liquid through sufficient stirring and ultrasonic dispersion. Inject the spray liquid into the ultrasonic spray equipment and lay the diaphragm to be sprayed on the work surface (use uncoated PE base film). Debug the ultrasonic spray parameters: the height of the nozzle from the diaphragm is 180mm; the speed of the nozzle relative to the diaphragm is 100mm / s, the spray liquid discharge speed is 1.5ml / min, and the ultrasonic power is 2W. Start spraying after the parameters are set. After the spraying is completed, wait for 2 minutes for the dispersant to volatilize, and finally form a functional coating on the surface of the diaphragm.
[0038] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a lithium battery separator having a functional coating on its surface, characterized in that: Using the ultrasonic spraying method, a two-dimensional nano-spraying material containing nitride or oxide is sprayed onto the surface of the battery separator to form a uniform protective layer.
2. The method for preparing a lithium battery separator having a functional coating on the surface according to claim 1, characterized in that: The spraying liquid includes coating material, adhesive and dispersant; the coating material and adhesive are mixed in a mass ratio of 8-10:1 and then added into the dispersant, and the mass fraction of solid matter is 30-50g / L.
3. The method for preparing a lithium battery separator having a functional coating on the surface according to claim 2, characterized in that: The coating material is at least one of molybdenum nitride, copper nitride, titanium nitride, nickel nitride, vanadium nitride, aluminum oxide, titanium oxide, silicon oxide and copper oxide.
4. The method for preparing a lithium battery separator having a functional coating on the surface according to claim 3, characterized in that: The coating material is in the shape of two-dimensional nanosheets, with a dimension in the thickness direction less than 10 nm and a dimension in the plane direction greater than 500 nm.
5. The method for preparing a lithium battery separator having a functional coating on the surface according to claim 2, characterized in that: The adhesive is at least one of polyurethane (TPU), polyacrylonitrile (PAN), polyethylene, polypropylene, poly(meth)acrylate, polymethyl (meth)acrylate, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroalkyl polymer (PFA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polysiloxane, polysilazane and polycarbosilane.
6. The method for preparing a lithium battery separator having a functional coating on the surface according to claim 2, characterized in that: The dispersant is at least one of ethylene glycol dimethyl ether (DME), N,N-dimethylformamide (DMF), dimethyl sulfone, diethyl sulfone, adiponitrile, tetrahydrofuran, N-methylpyrrolidone, acetonitrile, benzonitrile, 2-methyltetrahydrofuran, dioxolane, 4-methyldioxolane, N,N-dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, dichloroethane, chlorobenzene, ethanol, methanol and propanol.
7. The method for preparing a lithium battery separator having a functional coating on the surface according to claim 1, characterized in that: The diaphragm to be sprayed can be an uncoated base membrane or a diaphragm with a ceramic coating already present.
8. The method for preparing a lithium battery separator having a functional coating on the surface according to claim 1, characterized in that: Debug ultrasonic spraying parameters: the height of the nozzle from the diaphragm is 100-200mm; the nozzle moves at a speed of 50-100mm / s relative to the diaphragm, the spray liquid discharge speed is 0.5-2ml / min, and the ultrasonic power is 1-4W; after the parameters are set, start spraying; after starting spraying, the nozzle airflow needs to be kept stable at about 20L / min.
9. A lithium battery separator having a functional coating on its surface, prepared by the method for preparing a lithium battery separator having a functional coating on its surface as described in any one of claims 1 to 8.
10. A lithium battery, characterized in that: A lithium battery separator having a functional coating on its surface as described in claim 9.
Citation Information
Cited By
Battery monomer, battery device, power utilization device and energy storage device
CN121885720A
A battery cell, a battery device, a power consumption device, an energy storage device
CN121885720B